Indikator Ekonomi Berpengaruh Terhadap Deforestasi Di Indonesia - Hisyam Basymeleh; Irzameingindra Putri Radjamin; Olivia Tanaya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Economic growth is a benchmark for the success of a country's economic development. Economic development in a region is seen from several economic indicators such as per capita consumption, government spending, domestic investment, and business sector GDP. Deforestation is a phenomenon that is of global concern because of its harmful impact on the sustainability of human civilization on earth. The correlation between economic growth and deforestation has been confirmed, but there is still a lack of understanding of the factors and mechanisms underlying this relationship. The aim of this research is to determine the relationship between consumption, spending, investment and business GDP on deforestation in Indonesia. This research method uses a quantitative approach. The data used in this research is secondary data, regarding the variables used in this research, specifically: area of deforestation, average per capita consumption, government spending, gross domestic product (GDP) of business fields, and domestic government investment. The research results show that simultaneously consumption, government spending, investment and business GDP have a significant effect on deforestation, partially, consumption and business GDP have a significant effect on deforestation, while government spending and investment have no significant effect on deforestation. The government should encourage sustainable consumption patterns, for example through public awareness campaigns. The government can also consolidate aspects of sustainable environmental protection and empowerment in development plans and APBN/APBD as well as strengthen regulations and supervision of investment sectors that have the potential to cause deforestation.